Corporate sustainability: a case study of some industrial enterprises in Sétif Province - Djehnit, Amira; Kourtel, Farid (Journal of Human Sciences, 2021)
A growing number of researchers over the last few decades have recognized that the activities of an enterprise impact upon the external environment and have suggested that such an enterprise should therefore be accountable to a wider audience than simply its shareholders. Such a suggestion probably first arose in the 1970s and a concern with a wider view of enterprise performance is taken by some writers who evince concern with the social performance and the environmental performance of a business, as a member of society at large. Seeing enterprise as part of a broader socio-economic system implies that internal and external influences must be taken into account, not only measuring the costs and value created in the present but also for the future of the enterprise itself.And In the midst of a fundamental gap between theoretical assertions of a sustaincentric business paradigm and any rigorous empirical examination of its adoption the enterprise level Through our article, we seek to advance the field of corporate sustainability, as we aim through this paper to demonstrate the extent to which industrial enterprises in Setif have adopted the dimensions of sustainability